Protean Career of University Education Student - Pradinavika, Rifki (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
In the 21st century there is a new career contract that becomes part of everyday work life called a protean career which is characterized by actions that lead to self-directed and focus on intrinsic values in the pursuit of psychological success. This study aims to obtain a description of the protean career of university education student. The research was conducted using a quantitative approach and survey methods. Data were collected using a questionnaire of a five-level Likert scale which was adopted from the Protean Career Attitudes Scale (PCAS) developed by Briscoe et al (2006). Data were analyzed using the Rasch Model. The participants were 261 of university education student. The results showed that 82 students (31.4%) in transformational or protean career category, 36 students (13.8%) in reactive category, 43 students (16.5%) in rigid category, 100 students (38.3%) dependent category. In general, protean career of university education student are in the protean dependent career category, namely low on self-directed and values-driven aspects which are characterized by being unable to set priorities or manage their own careers.